Effect of Diabetes Self-Management Education on Self-Care Management Among Patients with Type 2 Diabetes Mellitus in Gedangan - Endah Palupi; Eka Diah Kartiningrum; Arief fardiansyah; Revi Ekasetya Pratiwi (Promotif : Jurnal Kesehatan Masyarakat, 2025)
Introduction: Patients with diabetes mellitus continue to face difficulties in performing self-care management based on the information they receive. Diabetes Self-Management Education (DSME) can serve as a reference for health education programs to improve patients’ knowledge and self-care management skills. This study aimed to analyze the effect of DSME on self-care management among patients with type 2 diabetes mellitus. Methods: This study employed a quasi-experimental two-group pre–posttest control design. The sample was 102 patients with type 2 diabetes mellitus selected using simple random sampling. The instrument utilized was the Diabetes Management Self-Efficacy Scale (DMSES). Data were analyzed using Wilcoxon test and multivariate ANOVA. Results: The results of the multivariate analysis showed a p-value < 0.001, indicating that Diabetes Self-Management Education (DSME) had a significant effect on self-care management, including dietary patterns (R² = 0.313), physical activity (R² = 0.737), blood glucose monitoring (R² = 0.430), foot care (R² = 0.427), and medication adherence (R² = 0.349) among patients with type 2 diabetes mellitus. Physical activity demonstrated the most significant effect attributable to DSME. Conclusion: Diabetes Self-Management Education (DSME) effectively improves self-care management in patients with type 2 diabetes mellitus, with the greatest impact on physical activity. These findings support DSME as an evidence-based strategy to promote independent self-care and as a standard operating protocol in Gedangan Community Health Center.